Effects of different types of refractive errors on bilateral amblyopia - Mücella Arıkan Yorgun (Modestum Publishing LTD, 2012)
Objectives: Identifying effects of different types of refractiveerrors on final visual acuity and stereopsis levels inpatients with bilateral amblyopia.Materials and methods: Patients with bilateral amblyopialower than ≥1.5 D anisometropia were included. Thepatients were classified according to the level of sphericalequivalent (0-4 D and >4 D of hypermetropia), the levelof astigmatism (below and above 2D in positive cylinder)and type of composed refractive error [<4 D of hypermetropiaand < 2 D of astigmatism (group I), > 4 D of hypermetropiaand < 2 D of astigmatism (group II), and < 4 Dhypermetropia and > 2 D of astigmatism (group III)]. Initialand final binocular best corrected visual acuities (BCVA)were compared between groups.Results: The initial binocular BCVA levels were significantlylower in patients with > 4 D of hypermetropia(p=0.028), without correction after treatment (p=0.235).The initial binocular BCVA was not different betweenastigmatism groups, but final BCVA levels were significantlylower in 4-6D of astigmatism compared with 2-4D of astigmatism (p=0.001). During comparison of composedrefractive errors, only the initial binocular BCVAwas significantly lower in group I compared to group II(p=0.015). The final binocular BCVA levels were not differentbetween groups I and III (p>0.05).Conclusions: Although the initial BCVA is lower in patientswith higher levels of hypermetropia, the response ofpatients to treatment with glasses is good. The responseof patients with high levels of astigmatism seems to belimited. J Clin Exp Invest 2012; 3(4): 467-471Key words: Amblyopia, isoametropic amblyopia, hypermetropia,refractive amblyopia, visual acuity